Interplay between the microalgae Micrasterias radians and its symbiont Dyadobacter sp. HH091 - Astafyeva, Yekaterina; Gurschke, Marno; Streit, Wolfgang R.; Krohn, Ines (Frontiers in Microbiology, 2022)
Based on previous research, related to detailed insight into mutualistic col-laboration of microalga and its microbiome, we established an artificial plant-bacteria system of the microalga Micrasterias radians MZCH 672 and the bacterial isolate Dyadobacter sp. HH091. The bacteria, affiliated with the phylum Bacteroidota, strongly stimulated growth of the microalga when it was added to axenic algal cul-tures. For further advances, we studied the isolate HH091 and its interaction with the microalga M. radians using transcriptome and extensive genome analyses. The genome of HH091 contains predicted polysaccharide utilizing gene clusters co-working with the type IX secretion system (T9SS) and conceivably involved in the algae-bacteria liaison. Here, we focus on characterizing the mechanism of T9SS, implementing the attachment and invasion of microalga by Dyadobacter sp. HH091. Omics analysis exposed T9SS genes: gldK, gldL, gldM, gldN, sprA, sprE, sprF, sprT, porU and porV. Besides, gld genes not considered as the T9SS components but re-quired for gliding motility and protein secretion (gldA, gldB, gldD, gldF, gldG, gldH, gldI, gldJ), were also identified at this analysis. A first model of T9SS apparatus of Dyadobacter was proposed in a course of this research. Using the combination of fluorescence labeling of Dyadobacter sp. HH091, we examined the bacterial coloni-sation and penetration into the cell wall of the algal host M. radians MZCH 672.